EFEKTIVITAS MEDIA VIDEO INTERAKTIF DALAM MENINGKATKAN PEMAHAMAN TEKNIK DASAR SENAM LANTAI PADA PEMBELAJARAN PJOK - Fadel Kurniawan Marto; Anggraeni, Emayanti; Mukharrar Fadjri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Floor gymnastics instruction in physical education classes is still dominated by conventional methods, resulting in suboptimal understanding of basic techniques among students, particularly in terms of visualizing complex movements. This limitation indicates a need for more interactive and effective learning media. This study aims to analyze the effectiveness of interactive video media in improving the understanding of basic floor gymnastics techniques in PJOK learning. The study uses a quantitative approach with a quasi-experimental design through a nonequivalent control group design. The study population consists of students who take PJOK lessons, with a sample of two groups consisting of an experimental group and a control group. Data were collected through floor gymnastics technique comprehension tests and analyzed using descriptive statistics, t-tests, and N-Gain. The results showed that the experimental group had higher learning outcomes that were significantly different from those of the control group. Thus, interactive video media proved to be effective in improving the understanding of basic floor gymnastics techniques and is recommended as an innovative and effective alternative learning medium for PJOK.